RETRACTED: Environmental Risk Assessment of Dexamethasone Sodium Phosphate and Tocilizumab Mixture in Zebrafish Early Life Stage (Danio rerio) - Davide Di Paola; Jessica Maria Abbate; Carmelo Iaria; Marika Cordaro; Rosalia Crupi; Rosalba Siracusa; Ramona D’Amico; Roberta Fusco; Daniela Impellizzeri; Salvatore Cuzzocrea; Nunziacarla Spanò; Enrico Gugliandolo; et al. (Toxics)
Pharmaceuticals are widely regarded as a menace to the aquatic environment. The constant consumption of biologically active chemicals for human health has been matched by an increase in the leaking of these compounds in natural habitats over the last two decades. This study was aimed to evaluate the molecular pathway underling the developmental toxicity of exposure in the ecological environment. Zebrafish embryos were exposed at doses of dexamethasone sodium phosphate (DEX) 1 μmol/L, tocilizumab 442.1 μmol/L and dexamethasone + tocilizumab (1 μmol/L and 442.1 μmol/L, respectively) from 24 h post-fertilization (hpf) to 96 hpf. This study confirmed that DEX exposure in association with tocilizumab 442.1 μmol/L at 1 μmol/L (non-toxic concentration) affected the survival and hatching rate, morphology score, and body length. Additionally, it significantly disturbed the antioxidant defense system in zebrafish larvae. Furthermore, a DEX 1 μmol/L and tocilizumab 442.1 μmol/L association also increased the production of apoptosis-related proteins (caspase-3, bax, and bcl-2).